Mitigasi Love Scamming: Penegakan dan Perlindungan Hukum Tindak Pidana Pemerasan Bermodus Cinta - Putra, Dika Anggara; Rosita, Dian (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2025)
The development of technology and social media has significantly changed the way people communicate, including in searching for life partners. However, this advancement has also created opportunities for cybercrimes, one of which is love scamming, a form of extortion using romance as a pretext through online platforms. Law enforcement against perpetrators of this crime is more relevant when applied under Article 27B paragraph (1) in conjunction with Article 45 paragraph (8) and Article 29 in conjunction with Article 45B of Law Number 1 of 2024, which amends Law Number 11 of 2008 concerning Electronic Information and Transactions. Although the primary element of love scamming is extortion, many cases also involve threats, making it possible to apply multiple legal provisions under the Indonesian Penal Code and the Electronic Information and Transactions Law. Legal protection for victims is carried out through two approaches: preventive and repressive. Preventive protection involves raising public awareness through education and outreach regarding romance-based scams on social media, while repressive protection includes concrete actions by the government and private organizations to help victims obtain legal protection and restore their rights. Therefore, social media users must be more cautious when interacting online, be able to distinguish between real and fake accounts, and avoid trusting strangers too easily to prevent becoming victims of love scamming.